Do we really value identified lives more highly than statistical lives? - Louise B. Russell (Rutgers University, Department of Economics, 2014)
Value of Statistical Life (VSL) studies suggest that people's willingness to pay for statistical lives is consistent with their willingness to pay for identified lives. The idea that the valuations are different may be no more than an artifact of the economic method for valuing statistical lives, the human capital approach, that was dominant at the time the distinction was proposed.
Keywords: D6; I1; H4; 330; Value of Statistical Life; Identified Lives